Sibutramine in pregnancy - Finan, Ramzi (2005)
Sibutramine hydrochloride monohydrate is an orally administered agent for the treatment of obesity. Chemically, the active ingredient is a racemic mixture of (+) and (−) enantiomers of cyclobutanemethanamine [1]. It produces its therapeutic effect by norepinephrine, serotonin, and dopamine reuptake inhibition, and it exerts its pharmacologic actions via two active metabolites M1 and M2 [1,2]. Menstrual irregularities along with elevation in blood pressure and heart rate have been reported with the use of sibutramine.